Maternal Prenatal Hair Cortisol Is Associated with Child Wheeze among Mothers and Infants with Tobacco Smoke Exposure and Who Face High Socioeconomic Adversity - Scherman, Ashley (Int J Environ Res Public Health, 2021)
The association of co-occurring prenatal stress and tobacco exposures on childhood wheezing and asthma are not well established. In this study, we compared maternal prenatal hair cortisol concentration (HCC) to the maternal report of infant wheezing (y/n) in the first year of life among mother–infant dyads exposed to tobacco smoke and socioeconomic adversity. Data were obtained from the Vitamin C to Decrease Effects of Smoking in Pregnancy on Infant Lung Function study. Maternal adversity was defined by the level of education, household income, and health insurance provider. Hair was collected at delivery, representing average circulating third-trimester cortisol levels. HCC was log transformed and dichotomized into high/low cortisol groups that were placed into a multivariate model predicting wheeze. Subjects (n = 132) were primarily White with ≤high school education and receiving government-provided health insurance. Forty-five percent of infants wheezed. Average HCC was 3.39 pg/mg hair. Women with HCC > 3.55 pg/mg were more than twice as likely to report having a child who wheezed (odds ratio 2.56, 95% confidence interval 1.22–5.40; p = 0.01), adjusting for insurance provider and maternal asthma. Among this sample of dyads with prenatal smoke exposure, elevated maternal HCC was associated with child wheeze that was not diminished after consideration of covariates.